Arahan Penjagaan Frenotomi Bayi (Lidah) - Harun, Nor Asilah; Ardini, Yunita Dewi; Jamani, Nurjasmine Aida; Samsuri, Aiman Hizami (2021)
It is information on how to take care of an infant/children after a frenotomy procedure